PUSAT OLAHRAGA BOLA VOLI TANAH BUMBU - Yudha Anggit Pangestu; Prima Widia Wastuty (JURNAL TUGAS AKHIR MAHASISWA LANTING, 2021)
The design of the Tanah Bumbu Volleyball Sports Center was motivated by the many people’s interest in Tanah Bumbu Regency in the sport of volleyball. With quite a lot of public interest, but the existing volleyball sport facilities and infrastructure are quite limited because there is only an outdoor volleyball field and the existing volleyball sport field standards are still lacking. The purpose of designing the Tanah Bumbu Volleyball Sport Center is as a place that complies with the standards to accommodate all volleyball sports and activities. The application of the concept of standardization by applying standards to the design is found in the plan, appearance, interior layout, outer space and color.